The Economic Impact of COVID-19 Lockdown on Malay Trans Women in Malaysia: A Qualitative Study - Fathima Begum Syed Mohideen; Nizam Baharom; Mohamed Fakhri Abu Baharin; Khadijah Hasanah Abang Abdullah; Rafidah Hanim Mokhtar; Zainora Daud (USIM Press, 2024)
Jurnal Sains Insani Volume 8 No.2 Page (226-236)